Histamine elicits glutamate release from cultured astrocytes - Anikó Kárpáti; Takeo Yoshikawa; Tadaho Nakamura; Tomomitsu Iida; Takuro Matsuzawa; Haruna Kitano; Ryuichi Harada; Kazuhiko Yanai (Elsevier, 2018)
Astrocytes play key roles in regulating brain homeostasis and neuronal activity. This is, in part, accomplished by the ability of neurotransmitters in the synaptic cleft to bind astrocyte membrane receptors, activating signalling cascades that regulate concentration of intracellular Ca2+ ([Ca2+]i) and gliotransmitter release, including ATP and glutamate. Gliotransmitters contribute to dendrite formation and synaptic plasticity, and in some cases, exacerbate neurodegeneration. The neurotransmitter histamine participates in several physiological processes, such as the sleep-wake cycle and learning and memory. Previous studies have demonstrated the expression of histamine receptors on astrocytes, but until now, only a few studies have examined the effects of histamine on astrocyte intracellular signalling and gliotransmitter release. Here, we used the human astrocytoma cell line 1321N1 to study the role of histamine in astrocyte intracellular signalling and gliotransmitter release. We found that histamine activated astrocyte signalling through histamine H1 and H2 receptors, leading to distinct cellular responses. Activation of histamine H1 receptors caused concentration-dependent release of [Ca2+]i from internal stores and concentration-dependent increase in glutamate release. Histamine H2 receptor activation increased cyclic adenosine monophosphate (cAMP) levels and phosphorylation of transcription factor cAMP response-element binding protein. Taken together, these data emphasize a role for histamine in neuron-glia communication. Keywords: Astrocyte, Calcium, Gliotransmitter, Glutamate, Histamine